Synthetic approaches to bowl-shaped π-conjugated sumanene and its congeners - Alvi, Shakeel; Ali, Rashid (Beilstein Journal of Organic Chemistry, 2020)
Since the first synthetic report in 2003 by Sakurai et al., sumanene (derived from the Indian ‘Hindi as well as Sanskrit word’ “Suman”, which means “Sunflower”), a beautifully simple yet much effective bowl-shaped C3-symmetric polycyclic aromatic hydrocarbon having three benzylic positions clipped between three phenyl rings in the triphenylene framework has attracted a tremendous attention of researchers worldwide. Therefore, since its first successful synthesis, a variety of functionalized sumanenes as well as heterosumanenes have been developed because of their unique physiochemical properties. For example, bowl-to-bowl inversion, bowl depth, facial selectivity, crystal packing, metal complexes, intermolecular charge transfer systems, cation–π complexation, electron conductivity, optical properties and so on. Keeping the importance of this beautiful scaffold in mind, we compiled all the synthetic routes available for the construction of sumanene and its heteroatom derivatives including Mehta’s first unsuccessful effort up to the latest achievements. Our major goal to write this review article was to provide a quick summary of where the field has been, where it stands at present, and where it might be going in near future. Although several reviews have been published on sumanene chemistry dealing with different aspects but this is the first report that comprehensively describes the ‘all-in-one’ chemistry of the sumanene architecture since its invention to till date. We feel that this attractive review article will definitely help the scientific community working not only in the area of organic synthesis but also in materials science and technology.
Keywords: buckybowls; heterosumanenes; polyaromatic hydrocarbons; sumanene; synthesis